Engineering Properties of Foods - Rao, M. A.; Rizvi, S. S. H.; Datta, Ashim K.; Ahmed, Jasimuddin (CRC Press, 2014)
Through three editions, this has been the must-have resource on food properties and their variations. The book defines food properties and the necessary theoretical background for each. It also evaluates the usefulness of each property in the design and operation of important food processing equipment. This new edition addresses advanced knowledge of food properties by providing the latest developments in the field. It offers three new chapters covering glass transition temperature pertaining to food, kinetics related to non-thermal processing, and micro-structural properties of foods.